Predicting Internet of Things (IOT) Security and Privacy Risks – A Proposal Model: توقع مخاطر أمن وخصوصية إنترنت الأشياء (IOT) – نموذج مقترح بحثي - Awad Saad Al-Qahtani, Mohammad Ayoub Khan (Journal of engineering sciences and information technology, 2021)
The Internet of things (IOT) users lack awareness of IOT security infrastructure to handle the risks including Threats, attack and penetration associated with its use. IOT devices are main targets for cyber-attacks due to variable personally identifiable information (PII) stored and transmit in the cyber centers. The security risks of the Internet of Things aimed to damage user's security and privacy. All information about users can be collected from their related objects which are stored in the system or transferred through mediums among diverse smart objects and may exposed to exposed dangerous of attacks and threats if it lack authentication so there are essential need to make IOT security requirements as important part of its efficient implementation. These requirements include; availability, accountability, authentication, authorization, privacy and confidentiality, Integrity and Non-repudiation. The study design is a survey research to investigate the visibility of the proposed model of security management for IOT uses, the security risks of IOT devices, and the changes IOT technology on the IT infrastructure of IOT users through answering of the research questionnaires. This work proposes a model of security management for IOT to predict IOT security and privacy threats, protect IOT users from any unforeseen dangers, and determine the right security mechanisms and protocols for IOT security layers, as well as give the most convenient security mechanisms. Moreover, for enhancing the performance of IOT networks by selecting suitable security mechanisms for IOT layers to increase IOT user's security satisfaction.